2013
DOI: 10.1177/0260106014563448
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indices and dietary intake

Abstract: Cognitive abnormalities doubly elevate with advancing age, with decreased intake of dietary nutrients. The cognitive assessment undertaken focused on this rampant under-diagnosed cognition. The burgeoning prodromal insidious stage of cognitive impairment demands rapid diagnosis for preserving mental health, or else severe deterioration takes over, leading to compromised mental abilities in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
1
1
Order By: Relevance
“…15 Research in India pointed to the reciprocal relationship between reduced dietary intake and cognitive function in elderly patients. 16 In the present study, females were more prone to loss of appetite than males. Other studies reported that females suffered more frequently from loss of appetite and were more prone to be underweight than males; this was also observed in our study, as the prevalence of malnutrition was significantly higher in females after controlling for other factors.…”
Section: Discussionsupporting
confidence: 42%
“…15 Research in India pointed to the reciprocal relationship between reduced dietary intake and cognitive function in elderly patients. 16 In the present study, females were more prone to loss of appetite than males. Other studies reported that females suffered more frequently from loss of appetite and were more prone to be underweight than males; this was also observed in our study, as the prevalence of malnutrition was significantly higher in females after controlling for other factors.…”
Section: Discussionsupporting
confidence: 42%
“…In contrast to our ndings, several studies have demonstrated that a higher BMI increases the risk of developing dementia later in life [28][29][30]. Moreover, overweight individuals are more likely to experience chronic illnesses [31] and decreased physical abilities [32], which can lead to cognitive decline.…”
Section: Discussioncontrasting
confidence: 89%
“…Since our results support the obesity paradox, we looked into the underlying mechanisms. One potential mechanisms is the association between aging, cognitive impairment and physical frailty [30,45], which is in uenced by factors such as chronic in ammation, nutrition, vascular diseases, depression, and endocrine problems [46][47][48]. Frailty is accelerated by age and failure of complex systems in older adults, which can cause functional and cognitive impairment [49,50].…”
Section: Discussionmentioning
confidence: 99%